KERAGAMAN MORFO-FISIOLOGI BENIH SUREN (Toona sinensis) DARI BERBAGAI TEMPAT TUMBUH DI SUMATERA DAN JAWA - Dharmawati F Djam'an; Dede Jajat Sudrajat (Jurnal Pemuliaan Tanaman Hutan, 2017)
Suren (Toona sinensis) is a potential multipurpose species that is more cultivated at upland community forests, especially in Java and Sumatra islands. This research was aimed to assess the variation of fruit and seed morpho-physiological characters and to investigate the contribution of geoclimate and genetic factors on the fruit and seed morpho-physiological characters of suren. Seeds were collected from seven populations in West Sumatera, Jambi and West Java on March – May 2015. Morphological parameters measured were size and weight of fruits and seeds, while the physiological parameters measured were seed germination and storability. Analysis of variance revealed significant morpho-physiological differences among populations for all the morpho-physiological parameters studied. Cimalaka population provided the better seed quality compared to seed quality from the other populations, mainly for seed physiological parameters. Most of the parameters was not correlated with geo-climate factors, except for number of empty seed that negatively correlated with mean annual temperature and seed wing width negatively correlated with altitude. Genotypic variance and genotypic coefficient of variance for all fruit and seed parameters were found to be higher than corresponding environment variance and environment coefficient of variance, indicating that the genotype explained most of the variance for these parameters. In particular, high heritability values coupled with high genetic gain were found for germination capacity and germination speed. Principal component analysis of various parameters of fruit and seed revealed that most of the geographically distant populations are genetically close.